Investigating the Role of Assessment Method on Reports of Déjà Vu and Tip-of-the-Tongue States during Standard Recognition Tests - Jersakova, Radka; Moulin, Chris J. A.; O’Connor, Akira R. (PLOS ONE, 2016)
Déjà vu and tip-of-the-tongue (TOT) are retrieval-related subjective experiences whose study relies on participant self-report. In four experiments (ns = 224, 273, 123 and 154), we explored the effect of questioning method on reported occurrence of déjà vu and TOT in experimental settings. All participants carried out a continuous recognition task, which was not expected to induce déjà vu or TOT, but were asked about their experiences of these subjective states. When presented with contemporary definitions, between 32% and 58% of participants nonetheless reported experiencing déjà vu or TOT. Changing the definition of déjà vu or asking participants to bring to mind a real-life instance of déjà vu or TOT before completing the recognition task had no impact on reporting rates. However, there was an indication that changing the method of requesting subjective reports impacted reporting of both experiences. More specifically, moving from the commonly used retrospective questioning (e.g. “Have you experienced déjà vu?”) to free report instructions (e.g. “Indicate whenever you experience déjà vu.”) reduced the total number of reported déjà vu and TOT occurrences. We suggest that research on subjective experiences should move toward free report assessments. Such a shift would potentially reduce the presence of false alarms in experimental work, thereby reducing the overestimation of subjective experiences prevalent in this area of research.